2015
DOI: 10.1177/0269215515596054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of very early mobilisation on functional status in patients with acute stroke: a single-blind, randomized controlled trail

Abstract: The results indicate that very early mobilisation in addition to the standard care may be effective in improving the functional status following acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 14 publications
2
39
1
4
Order By: Relevance
“…Results are presented as the OR (95% CI) of the early versus delayed mobilisation group. 65 Bernhardt 35 AVERT 31 Chippala 60 Chippala 63 Poletto 61 Herisson 62 T his project met its initial objectives of effectively delivering our VEM protocol with a resulting change in practice. 30 We observed earlier, more frequent and higher dose (amount of) out-of-bed mobility in terms of sitting, standing and walking activity.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are presented as the OR (95% CI) of the early versus delayed mobilisation group. 65 Bernhardt 35 AVERT 31 Chippala 60 Chippala 63 Poletto 61 Herisson 62 T his project met its initial objectives of effectively delivering our VEM protocol with a resulting change in practice. 30 We observed earlier, more frequent and higher dose (amount of) out-of-bed mobility in terms of sitting, standing and walking activity.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
“…In our systematic review of similar RCTs, we identified eight eligible trials 25,27,31,[60][61][62][63][64] that currently have data available. Of these eight trials (2618 participants), AVERT provided the most information (2104 participants).…”
Section: Meta-analysis Of Early Mobilisation Trialsmentioning
confidence: 99%
“…Chippala et al [51] used a VEM protocol modeled after AVERT’s, with 5–30-min sessions of OOB activity at least twice a day for 7 days, beginning within 24 h of stroke onset, in addition to SC (defined as 45 min a day of passive and/or active exercises, with mobilization occurring at the therapists’ discretion). The primary outcome was change in functional status (Barthel Index [BI]) from baseline to hospital discharge.…”
Section: Human Trialsmentioning
confidence: 99%
“…6 The evidence-base behind some of these recommendations is not large, but there is some evidence supporting the involvement of rehabilitation in parallel with medical care. The benefits of early mobilization after acute-onset disability [7][8][9][10] and the risks of bed-rest and immobility are well established. There remains uncertainty whether 'aggressive' mobilization very early after stroke is beneficial.…”
Section: Rehabilitation As a Parallel Servicementioning
confidence: 99%